All-solid-state battery cell, solid electrolyte powder, method for producing solid electrolyte powder, and method for producing cover

By using a cover layer composed of lithium-ion conductive oxides and a new solid electrolyte powder in an all-solid lithium-ion battery, the problems of increasing interface resistance between the positive electrode active substance and the solid electrolyte are solved and the battery capacity is achieved Improvement and energy density.

CN119497921APending Publication Date: 2025-02-21DOWA HOLDINGS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480002868.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-10
Filing Date
2024-04-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In all-solid lithium-ion batteries, the interface resistance between the positive electrode active material and the solid electrolyte increases, resulting in a decrease in battery capacity, and the existing solid electrolyte is prone to deterioration under high charging voltage.

Method used

A solid electrolyte covering layer composed of lithium ion conductive oxides (such as LiNbO3) is used to cover the surface of the positive electrode active material to avoid its reaction with the solid electrolyte, and a new solid electrolyte powder is developed, which contains a specific proportion of Li, Nb and P, the crystallite diameter is less than 100 nm.

Benefits of technology

It effectively reduces the interface resistance, improves the energy density and output characteristics of the battery, and slows down the deterioration of the solid electrolyte under high charging voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497921A_ABST
    Figure CN119497921A_ABST
Patent Text Reader

Abstract

Provided are: a solid electrolyte powder which contains 0.7-5% by mass of Li, 8-60% by mass of Nb, and 1.0-30% by mass of P, with respect to the solid electrolyte powder, and in which the content of a non-oxygen remainder other than oxygen (O) is 10% by mass or less with respect to the solid electrolyte powder, and which has a crystallite diameter of 100 nm or less; and a technique relating to the solid electrolyte powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an all-solid-state battery cell, a solid electrolyte powder, a method for producing the solid electrolyte powder, and a method for producing a covering body. Background Art

[0002] In an all-solid lithium-ion secondary battery (hereinafter sometimes referred to as an "all-solid battery"), a solid electrolyte is arranged as a separator between the positive electrode active material and the negative electrode active material, and the conduction of lithium ions between the two active materials is carried out by means of the solid electrolyte. As the solid electrolyte, various sulfide-based, oxide-based, polymer-based solid electrolytes have been developed. With regard to ion conductivity and manufacturing cost, sulfide-based solid electrolytes are currently considered to be advantageous.

[0003] In all-solid batteries, the interface resistance between the positive electrode active material and the solid electrolyte as a separator increases, and there is a problem that the battery capacity and other performance are easily reduced. The increase in interface resistance is mainly due to the reaction between the positive electrode active material and the solid electrolyte to form a high resistance site on the surface of the positive electrode active material, which is easy to become a problem when using a sulfide-based solid electrolyte as a separator.

[0004] Therefore, attempts have been made to cover the surface of the positive electrode active material with a solid electrolyte as a protective material composed of a lithium ion conductive oxide (representatively, well-known LiNbO3) or a halide to prevent the positive electrode active material from reacting with the solid electrolyte as a separator.

[0005] Claim 1 of Patent Document 1 discloses an all-solid lithium battery, characterized in that, in an all-solid lithium battery using a lithium ion conductive solid electrolyte as an electrolyte, the aforementioned lithium ion conductive solid electrolyte is mainly composed of sulfide, and the surface of the positive electrode active material is covered with a lithium ion conductive oxide.

[0006] Patent Document 2 describes the following.

[0007] If the voltage of the working electrode of the electrochemical cell is scanned toward the oxidation side, a current originating from a non-Faraday reaction without electron transfer or a small current originating from a side reaction of water or impurities adsorbed on the surface of the conductive additive flows. After that, an excessive current of oxidative decomposition of the solid electrolyte begins to flow. In the test example described in Patent Document 2, the voltage at which a current value of 3 μA or more begins to flow is defined as an oxidative decomposition voltage.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: WO2007 / 004590 Pamphlet

[0011] Patent Document 2: WO2020 / 174868 Pamphlet Summary of the invention

[0012] Problem that the invention aims to solve

[0013] In recent years, there has been an increasing desire to improve the output characteristics and energy density of all-solid batteries. Therefore, a solid electrolyte having high lithium ion conductivity and a high decomposition voltage is required. The decomposition voltage refers to the oxidation decomposition voltage described in Patent Document 2.

[0014] The solid electrolyte as a protective material deteriorates when a high charging voltage is applied. In the case of LiNbO3, which is a protective material described in Patent Document 1 and a representative protective material, the degradation is accelerated if the charging voltage exceeds 4.45 V. In other words, in the case of LiNbO3, which is a protective material described in Patent Document 1 and a representative protective material, the degradation is accelerated when the decomposition voltage exceeds 4.45 V.

[0015] An object of the present invention is to provide a solid electrolyte powder capable of achieving both high lithium ion conductivity and high decomposition voltage, a method for producing the same, and a method for producing a coating.

[0016] Another object of the present invention is to provide an all-solid-state battery cell having both high lithium ion conductivity and high decomposition voltage by using the solid electrolyte powder or a coating thereof.

[0017] Solutions for solving problems

[0018] The first invention is an all-solid-state battery cell comprising:

[0019] Conductive material on the high potential side,

[0020] a first solid electrolyte in contact with the conductive material on the high potential side,

[0021] a second solid electrolyte in contact with the first solid electrolyte, and

[0022] a conductive material on the low potential side in contact with the second solid electrolyte,

[0023] The first solid electrolyte contains at least one of the following solid electrolytes (1) and (2) as a main component,

[0024] The second solid electrolyte contains sulfide as a main component,

[0025] (1) A solid electrolyte containing 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P relative to the solid electrolyte, wherein the content of the remainder other than oxygen, i.e., O, is 10 mass % or less relative to the solid electrolyte, and the crystallite diameter is 100 nm or less,

[0026] (2) When the molar ratio of Li, Nb and P contained in the solid electrolyte is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, z is 5 to 65, and the crystallite diameter is less than 100 nm.

[0027] The second invention is the all-solid-state battery cell according to the first invention, wherein the first solid electrolyte is any of the following (3) and (4):

[0028] (3) containing 0.7 to 2.6 mass % of Li, 8 to 60 mass % of Nb, and 2.0 to 30 mass % of P relative to the solid electrolyte, and

[0029] When the molar ratio of Li, Nb and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less, the content of the non-oxygen remainder other than oxygen, i.e., O, in the remainder is 10% by mass or less relative to the solid electrolyte, and the crystallite diameter is 100 nm or less.

[0030] (4) When the molar ratio of Li, Nb and P contained in the solid electrolyte is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 30, y is 5 to 65, z is 5 to 65, and the crystallite diameter is less than 100 nm.

[0031] The third invention is the all-solid-state battery cell according to the first or second invention, wherein:

[0032] The conductive material on the high potential side includes a positive electrode active material and other conductive members.

[0033] The positive electrode active material is in contact with the first solid electrolyte, and the positive electrode active material is not in contact with the second solid electrolyte.

[0034] A fourth invention is the all-solid-state battery cell according to any one of the first to third inventions, wherein:

[0035] The conductive material on the high potential side includes a positive electrode active material and other conductive members.

[0036] The surfaces of the particles of the positive electrode active material are covered with the first solid electrolyte.

[0037] The fifth invention is a solid electrolyte powder, wherein:

[0038] The solid electrolyte powder contains 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P.

[0039] The content of the non-oxygen balance other than oxygen, that is, O, in the balance is 10% by mass or less relative to the solid electrolyte powder.

[0040] The crystallite diameter of the solid electrolyte powder is 100 nm or less.

[0041] The sixth invention is the solid electrolyte powder according to the fifth invention, wherein

[0042] The solid electrolyte powder contains 0.7 to 2.6 mass % of Li, 8 to 60 mass % of Nb, and 2.0 to 30 mass % of P, and

[0043] When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less.

[0044] A seventh invention is the solid electrolyte powder according to the fifth or sixth invention, wherein a content of the transition metal element in the non-oxygen remainder is 3% by mass or less relative to the solid electrolyte powder.

[0045] The eighth invention is a solid electrolyte powder, wherein:

[0046] When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65.

[0047] The crystallite diameter of the solid electrolyte powder is 100 nm or less.

[0048] A ninth invention is the solid electrolyte powder according to the eighth invention, wherein the content of non-oxygen remainder other than oxygen, ie, O, in the remainder is 10% by mass or less relative to the solid electrolyte powder.

[0049] The tenth invention is the solid electrolyte powder according to the eighth or ninth invention, wherein x is 15 to 30, y is 5 to 65, and z is 5 to 65.

[0050] The eleventh invention is the solid electrolyte powder according to any one of the fifth to tenth inventions, wherein the total mass % of Li, Nb, and P in the solid electrolyte powder of the present embodiment is within a range of 25 to 65 mass %.

[0051] The 12th invention is the solid electrolyte powder according to any one of the 5th to 11th inventions, wherein the particle size of the solid electrolyte powder is 5 to 50 μm, and the particle size is a volume-based cumulative 50% particle size (D50) obtained using a laser diffraction scattering particle size distribution analyzer.

[0052] The 13th invention is the solid electrolyte powder according to any one of the 5th to 12th inventions, which is used for an all-solid-state battery cell.

[0053] The 14th invention is an all-solid-state battery cell comprising:

[0054] Conductive material on the high potential side,

[0055] a first solid electrolyte in contact with the conductive material on the high potential side,

[0056] a second solid electrolyte in contact with the first solid electrolyte, and

[0057] a conductive material on the low potential side in contact with the second solid electrolyte,

[0058] The first solid electrolyte comprises the solid electrolyte powder according to any one of the fifth to thirteenth inventions as a main component,

[0059] The second solid electrolyte contains sulfide as a main component.

[0060] The fifteenth invention is a method for producing a solid electrolyte powder, which is the method for producing a solid electrolyte powder according to the fifth or eighth invention, comprising:

[0061] A step of dry-mixing a Li raw material, a Nb raw material, and a P raw material in an inert atmosphere with a dew point of -20°C or less to obtain a mixed powder; and

[0062] The mixed powder is calcined at 350° C. or lower in an air atmosphere.

[0063] The 16th invention is the method for producing a solid electrolyte powder according to the 15th invention, wherein the Li raw material is lithium oxide, the Nb raw material is hydrated niobium oxide, and the P raw material is phosphorus pentoxide.

[0064] The 17th invention is a method for producing a solid electrolyte powder, comprising:

[0065] a phosphate ion adding step of adding phosphate ions to an aqueous solution containing polyacid ions of niobium and lithium; and

[0066] a drying step of drying the aqueous solution obtained in the above-mentioned adding step to obtain a solid electrolyte powder,

[0067] When the molar ratio of Li, Nb and P in the aqueous solution obtained by the above-mentioned adding step is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65.

[0068] The 18th invention is a method for manufacturing a covering body, comprising:

[0069] A step of adding phosphate ions to an aqueous solution containing polyacid ions of niobium and lithium to obtain an aqueous solution in which x is 15 to 50, y is 5 to 65, and z is 5 to 65 when the molar ratio of Li, Nb, and P in the aqueous solution is Li:Nb:P=x:y:z (x+y+z=100); and

[0070] a covering step of bringing the aqueous solution obtained in the above step into contact with a positive electrode active material to cover the surface of the positive electrode active material with a solid electrolyte,

[0071] The solid electrolyte satisfies at least one of the following conditions:

[0072] i) containing 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P relative to the solid electrolyte,

[0073] The content of the non-oxygen balance other than oxygen, that is, O, in the balance is 10% by mass or less relative to the solid electrolyte, and

[0074] Solid electrolytes with crystallite diameters below 100 nm,

[0075] ii) when the molar ratio of Li, Nb and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65, and

[0076] Solid electrolyte with a crystallite diameter of less than 100nm.

[0077] Effects of the Invention

[0078] According to the present invention, it is possible to provide a solid electrolyte powder capable of achieving both high lithium ion conductivity and high decomposition voltage, a method for producing the solid electrolyte powder, and a method for producing a coating.

[0079] Furthermore, according to the present invention, by using the solid electrolyte powder or a coating thereof, it is possible to provide an all-solid-state battery cell having both high lithium ion conductivity and high decomposition voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 This is a schematic diagram of a cross-sectional structure of one form of the all-solid-state battery cell according to the present embodiment.

[0081] Figure 2 This is a schematic diagram of a cross-sectional structure of another form of the all-solid-state battery cell according to the present embodiment.

[0082] Figure 3 It is a schematic diagram of the cross-sectional structure of a lithium ion secondary battery that effectively utilizes the all-solid-state battery element of the present embodiment.

[0083] Figure 4 This is a flow chart of the method for producing the solid electrolyte powder of the present invention.

[0084] Figure 5 This is a graph showing the composition ratios of Li, Nb, and P in the solid electrolyte powder obtained in each example expressed in terms of molar ratio.

[0085] Figure 6 This is a graph showing the composition ratio of Li, Nb, and P in the solid electrolyte powder obtained in each example expressed by the molar ratio and the decomposition voltage as numerical values.

[0086] Figure 7 In the electrochemical evaluation of each example, the potential (unit is V (vsLi / Li + )) is the horizontal axis and the current value (unit is μA) is the vertical axis.

[0087] Figure 8 This is a graph in which 2θ (unit: °) is plotted on the horizontal axis and intensity (cps) is plotted on the vertical axis in the evaluation of the degree of crystallinity in each example.

[0088] Fig. 9 This is a flow chart for coating a positive electrode active material with a first solid electrolyte using the coating solution of the present invention.

[0089] Fig.10 It is a graph showing the FT-IR spectra of the aqueous solutions obtained in Comparative Example 2 and Example 10.

[0090] Fig.11 It is a schematic diagram of the cross-sectional structure of the electrochemical cell configured to investigate the discharge DCR increase rate in Comparative Example 2 and Example 10. DETAILED DESCRIPTION

[0091] Hereinafter, the embodiment of the present invention will be described. "-" means a value greater than or equal to a predetermined value and less than or equal to a predetermined value.

[0092] In this specification, "high potential side" means the side of the high potential electrode (positive electrode in a battery) in the charge path relative to the solid electrolyte as a separator disposed between the two electrodes. "Low potential side" means the side of the low potential electrode (negative electrode in a battery) in the charge path relative to the solid electrolyte as a separator disposed between the two electrodes.

[0093] This embodiment will be described in the following order.

[0094] 1. Solid electrolyte powder

[0095] 2. All-solid-state battery cells

[0096] 3. Lithium-ion secondary battery

[0097] 4. Method for producing solid electrolyte powder

[0098] [1. Solid electrolyte powder]

[0099] The solid electrolyte powder of the present embodiment mainly has the following configuration.

[0100] <Constitution 1> The solid electrolyte powder contains 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P. This constitution is also referred to as a "mass % expressed constitution".

[0101] <Configuration 2> The content of the non-oxygen balance other than oxygen, that is, O, in the balance is 10% by mass or less based on the solid electrolyte powder.

[0102] <Configuration 3> The crystallite diameter is 100 nm or less.

[0103] Regarding the above-mentioned configuration 1, if the amount of Li (lithium) contained in the solid electrolyte powder is 0.7 mass % or more and 5.0 mass % or less, it is a sufficient amount as a carrier and can ensure high lithium ion conductivity (hereinafter also referred to as ion conductivity). Specifically, it can ensure 5.0×10 -11 S / cm or more, preferably 5.0×10 -10 The ion conductivity is greater than 1.0 mass %, 1.1 mass %, 1.2 mass %, 1.3 mass %, or 1.4 mass %. The upper limit of the amount of Li contained in the solid electrolyte powder may be 4.0 mass %, 3.5 mass %, or 2.6 mass %.

[0104] When the amount of Nb (niobium) contained in the solid electrolyte powder is 8 mass % or more and 60 mass % or less, the solid electrolyte in the battery can fully function. The upper limit of the amount of Nb contained in the solid electrolyte powder may be 55 mass %.

[0105] If the amount of P (phosphorus) contained in the solid electrolyte powder is 1.0 mass % or more and 30 mass % or less, sufficient improvement in withstand voltage can be achieved. The lower limit of the amount of P contained in the solid electrolyte powder may be 2.0 mass %. The upper limit of the amount of P contained in the solid electrolyte powder may be 25 mass % or 20 mass %.

[0106] The decomposition voltage of the electrochemical cell produced by using the solid electrolyte powder of the following composition was measured to be 5.0 V or more, and the ion conductivity was 5×10 -10 S / cm or more, which is preferred.

[0107] "The solid electrolyte powder contains 0.7 to 2.6 mass% Li, 8 to 60 mass% Nb, and 2.0 to 30 mass% P, and when the molar ratio of Li, Nb and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less."

[0108] The method of obtaining the decomposition voltage and ion conductivity from the solid electrolyte powder is described in detail in the section of Examples, and the expression of the detailed contents as generalized as possible is described in the column of Means for Solving the Problems.

[0109] Regarding the above-mentioned configuration 2, in the solid electrolyte powder, the content of the remainder other than Li, Nb, and P excluding O (ie, non-oxygen remainder) is set to 10% by mass or less relative to the solid electrolyte powder.

[0110] The existence ratio (molar ratio) of oxygen is mainly determined by the valence of Li, Nb and P. That is, Li is +1, Nb is +5, P is +5, and oxygen is -2, and the amount of oxygen (set as the main oxygen amount) is determined in a way to compensate for the charge. The general formula is xLi2O-yNb2O5-zP2O5.

[0111] When the non-oxygen remainder contains elements other than Li, Nb, and P, the oxygen amount (referred to as the secondary oxygen amount) can be similarly calculated from the valence of the element. The non-oxygen remainder may contain H, C, N, other metal elements, semi-metal elements, and non-metal elements. For example, H is derived from H2O, C is derived from CO2, and N is derived from N2O5.

[0112] The amount of oxygen (molar ratio) can be calculated from the sum of the amount of primary oxygen and the amount of secondary oxygen, and the mass ratio of oxygen can be calculated by further performing mass conversion. In addition, the mass ratio of oxygen can also be measured by a known method such as an oxygen analyzer. This is particularly effective when the valence of the element other than the oxygen remainder is unclear.

[0113] According to the above provisions, it is clear that the majority (i.e., 90% by mass or more) of the solid electrolyte powder of this embodiment is composed of Li, Nb, P, and O. The content of the non-oxygen residual is preferably 5% by mass or less, and more preferably 1% by mass or less.

[0114] The content of the transition metal element (preferably the entire metal element) in the non-oxygen remainder is preferably 3% by mass or less based on the solid electrolyte powder.

[0115] Regarding the content of non-oxygen components, N (nitrogen) can be measured using a nitrogen analyzer, C (carbon) can be measured using a carbon / sulfur analyzer, and other elements can be measured by an inductively coupled plasma emission spectrometer (ICP-AES). The total value of the content (mass %) other than Li, Nb, P, and O obtained by these measurements is taken as the content of the non-oxygen balance.

[0116] A solid electrolyte powder containing Li, Nb, and P in amounts satisfying the above-mentioned composition 1 and having a crystallite diameter of less than 100 nm (i.e. satisfying the above-mentioned composition 3) has both high lithium ion conductivity and high decomposition voltage when processed into an all-solid-state battery cell, as shown in the items of the embodiments described later.

[0117] The composition of the solid electrolyte powder of the present embodiment can also be expressed as follows. That is, when the molar ratio of Li, Nb, and P of the solid electrolyte powder of the present embodiment is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, z is 5 to 65, and the crystallite diameter is 100 nm or less. This composition of x, y, and z is also referred to as a "molar ratio expression composition".

[0118] When x is 15 or more and 50 or less, the amount of carriers is sufficient, and high lithium ion conductivity (hereinafter also referred to as ion conductivity) can be ensured. Specifically, 5.0×10 -11 S / cm or above ionic conductivity.

[0119] x is preferably 30 or less.

[0120] When y is 5 or more and 65 or less, the function as a solid electrolyte in the battery can be sufficiently exhibited.

[0121] When z is 5 or more and 65 or less, sufficient improvement in withstand voltage can be achieved.

[0122] The decomposition voltage of the electrochemical cell prepared using the solid electrolyte powder with x being 15 to 30, y being 5 to 65, and z being 5 to 65 was measured to be 5.0 V or more, and the ion conductivity was 5×10 -10 S / cm or more, which is preferred.

[0123] In the above-mentioned configuration 3, the crystallite diameter of the solid electrolyte powder is specified to be 100 nm or less.

[0124] The crystallite diameter of the solid electrolyte powder is measured by powder X-ray diffraction (XRD), and is calculated using the Scherrer formula (Dhkl = Kλ / βcosθ) from the diffraction peak data observed in the region of 2θ: 15° to 40°. The crystallite diameter is preferably 50 nm or less. More preferably, it is 30 nm or less. Further preferred is an amorphous material in which a halo is observed in the X-ray diagram in the region of 2θ: 15° to 40°. It should be noted that "halo" means that in the X-ray diagram obtained by XRD measurement, no clear peak is shown in the region of 2θ: 15° to 40°, and it is observed as a wide bulge with gentle fluctuations in the intensity of the X-rays. Moreover, the half-peak width of the halo is greater than 2θ: 2°. If the crystallite diameter exceeds 100 nm, the solid electrolyte powder is not amorphous, and the ionic conductivity is reduced to less than 5×10 -10 S / cm.

[0125] It is preferable to combine the contents related to the above-mentioned composition 1 (ie, the expression in mass %) with the expression in the above-mentioned molar ratio. It is also preferable to combine the contents related to the above-mentioned composition 3 with the expression in the above-mentioned molar ratio.

[0126] With respect to the above expression in mass % or the above expression in molar ratio, the following constitutions may be combined.

[0127] The molar ratio of P to Li (P / Li) in the solid electrolyte powder of the present embodiment is preferably 0.2 or more and 3.5 or less. From the viewpoint of voltage resistance, it is more preferably 1.4 or more and 3.5 or less. The molar ratio of P to Nb (P / Nb) in the solid electrolyte powder of the present embodiment is preferably 0.1 or more and 6.5 or less. From the viewpoint of voltage resistance, it is preferably 1.4 or more and 6.5 or less, more preferably 3.0 or more and 6.5 or less, and further preferably 4.0 or more and 6.5 or less.

[0128] The total mass % of Li, Nb, and P in the solid electrolyte powder of the present embodiment is preferably in the range of 25 to 65 mass %.

[0129] The particle size of the solid electrolyte powder of the present embodiment is not particularly limited. The volume-based particle size distribution is measured using a laser diffraction scattering particle size distribution measuring device, and the volume-based cumulative 50% particle size (D50) obtained by the measurement is preferably 5 to 50 μm. From the perspective of ion conductivity, the volume-based cumulative 50% particle size (D50) is preferably 5 to 15 μm.

[0130] [2. All-solid-state battery cell]

[0131] The all-solid-state battery cell (in other words, the arrangement structure of the solid electrolyte) of the present embodiment mainly has the following configuration.

[0132] Conductive material on the high potential side

[0133] ·The first solid electrolyte in contact with the conductive material on the high potential side

[0134] A second solid electrolyte in contact with the first solid electrolyte

[0135] ·Conductive material on the low potential side in contact with the second solid electrolyte

[0136] The contents overlapping with those described in the above-mentioned [1. Solid electrolyte powder] are omitted below.

[0137] Figure 1 The cross-sectional structure of one embodiment of an all-solid-state battery having an all-solid-state battery cell of the present invention is schematically illustrated. In order to illustrate the positional relationship of each component, the figure ultimately depicts the structure of the cell in a simplified manner. The conductive material 3 on the high potential side and the conductive material 4 on the low potential side are opposed to each other, sandwiching the first solid electrolyte 1 and the second solid electrolyte 2 as a separator. The first solid electrolyte 1 is sandwiched between the conductive material 3 on the high potential side and the second solid electrolyte 2. There is a mutual contact portion between the conductive material 3 on the high potential side and the first solid electrolyte 1, and there is also a mutual contact portion between the first solid electrolyte 1 and the second solid electrolyte 2.

[0138] In an all-solid-state battery, the conductive material 3 on the high potential side is usually composed of a positive electrode active material 31 and a conductive material 32 other than the positive electrode active material. The positive electrode active material 31 is an ion conductive material and is also a conductive material. Its form is not limited and can be granular or powder. The conductive material 32 other than the positive electrode active material is a current collector, a conductive aid, etc. In addition to conductive components such as a current collector, a positive electrode active material, and a conductive aid, the positive electrode material in an actual all-solid-state battery is usually composed of particles of an ion conductive material (solid electrolyte) mixed in a manner that fills the spaces between the particles of the positive electrode active material. Figure 1 The conductive material 3 on the high potential side of the positive electrode material schematically illustrates the arrangement relationship of the portion of the positive electrode material constituted by the conductive member relative to the first solid electrolyte 1. In the illustrated form, the positive electrode active material 31 is in contact with the first solid electrolyte 1, and the ion conduction between the second solid electrolyte 2 as a separator and the positive electrode active material 31 is carried out via the first solid electrolyte 1. In addition, the positive electrode active material 31 is in contact with the conductive material 32 other than the positive electrode active material, so that the conduction between the external wiring member not shown and the conductive material 32 other than the positive electrode active material and the positive electrode active material 31 can be ensured.

[0139] As the positive electrode active material 31, in addition to the known materials, when a new positive electrode active material is developed, it can also be used. As representative known positive electrode active materials, LiCoO2 (LCO type), LiNiO2 (LNO type), LiMn2O4 (LMO type), LiNiCoAlO2 (NCA type), LiNiCoMnO2 (NCM type), Li2MnO3-LiNiCoMnO2 (solid solution type), LiNiMnO4 (spinel type), LiMnFePO4 (phosphate type), Li2FeSiO4 (silicate type), etc. can be listed.

[0140] The first solid electrolyte 1 contains at least one of the following solid electrolytes (1) and (2) as a main component.

[0141] (1) A solid electrolyte containing 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P relative to the solid electrolyte, wherein the content of the remainder other than oxygen, that is, O, is 10 mass % or less relative to the solid electrolyte, and the crystallite diameter is 100 nm or less.

[0142] (2) When the molar ratio of Li, Nb, and P is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, z is 5 to 65, and the crystallite diameter is less than 100 nm.

[0143] The "main component" mentioned here means that the substance whose total content in the constituent materials of the first solid electrolyte 1 is 50 mass% or more is a solid electrolyte that satisfies at least one of the conditions described in (1) and (2). The total content of the solid electrolyte that satisfies at least one of the conditions described in (1) and (2) in the constituent materials of the first solid electrolyte 1 is preferably 80 mass% or more, and more preferably 90 mass% or more.

[0144] The solid electrolyte may be a powder as described in [1. Solid electrolyte powder] above, or may be provided on the positive electrode in a manner other than this (e.g., in a layered or film-like form). Therefore, the term "solid electrolyte" is used in this item. However, for simplicity of description, the solid electrolyte powder is exemplified below.

[0145] The first solid electrolyte 1 preferably further satisfies the conditions described in the following (3) and (4).

[0146] (3) A solid electrolyte containing 0.7 to 2.6 mass % of Li, 8 to 60 mass % of Nb, and 2.0 to 30 mass % of P relative to the solid electrolyte, and when the molar ratio of Li, Nb, and P is set to Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less, and the content of the remainder other than oxygen, that is, O, is 10 mass % or less relative to the solid electrolyte, and the crystallite diameter is 100 nm or less

[0147] (4) When the molar ratio of Li, Nb, and P contained in the solid electrolyte is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 30, y is 5 to 65, z is 5 to 65, and the crystallite diameter is less than 100 nm

[0148] exist Figure 1 In the embodiment, the contact between the conductive material 3 on the high potential side and the second solid electrolyte 2 as a separator is completely blocked by the first solid electrolyte 1. Therefore, the reaction caused by the contact between the member constituting the conductive material 3 on the high potential side and the second solid electrolyte 2 mainly composed of sulfide or the like is avoided. That is, the first solid electrolyte 1 has a function as a protective material. In addition, as described later, when the first solid electrolyte 1 used in the present invention is arranged in contact with the second solid electrolyte 2 mainly composed of sulfide or the like, it has excellent resistance to degradation when a high voltage is applied, so Figure 1 The all-solid-state battery cell of the type shown is effective in improving the decomposition voltage.

[0149] From the viewpoint of ion conductivity and manufacturing cost, the second solid electrolyte 2 is mainly composed of sulfide and functions as a separator. "Mainly composed of sulfide" means that the total content of sulfide in the constituent materials of the second solid electrolyte 2 is 50% by mass or more. The total content of sulfide in the constituent materials of the second solid electrolyte 2 is preferably 80% by mass or more, and more preferably 90% by mass or more.

[0150] In addition to the known ion-conducting materials, the above-mentioned sulfides can also be used when new ion-conducting materials are developed. Representative known ion-conducting materials include Li6PS5Cl (crystal (argyrodite)), Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 (Crystal), Li 10 GeP2S 12(crystal), 30Li2S·26B2S3·44LiI (glass), 63Li2S·36SiS2·1Li3PO4 (glass), 57Li2S·38SiS2·5Li4SiO4 (glass), 70Li2S·30P2S5 (glass), Li7P3S 11 (Glass Ceramics), Li 3.25 P 0.95 S4 (glass ceramics), etc.

[0151] In an all-solid-state battery, the conductive material 4 on the low potential side is usually composed of a negative electrode active material 41 and a conductive material 42 other than the negative electrode active material. In addition to conductive components such as a current collector and a negative electrode active material, the negative electrode material in an actual all-solid-state battery is usually composed of particles of an ion conductive material (solid electrolyte) mixed in a manner that fills the space between particles of the negative electrode active material. Figure 1 The conductive material 4 on the low potential side schematically illustrates the configuration relationship of the portion of the negative electrode material composed of the conductive member relative to the second solid electrolyte 2. The configuration of the conductive material 4 on the low potential side and the configuration relationship between the conductive material 4 and the second solid electrolyte 2 can be the same as those of the known all-solid-state battery. It should be noted that the third solid electrolyte can also be configured between the second solid electrolyte 2 and the conductive material 4 on the low potential side as needed.

[0152] exist Figure 1 In the all-solid-state battery method shown, all of the conductive material 3 on the high potential side is separated from the second solid electrolyte (sulfide, etc.) serving as a separator by the interposition of the first solid electrolyte 1, so that the decomposition voltage can be improved without covering the surface of the particles of the positive electrode active material 31 with a solid electrolyte serving as a protective material.

[0153] Figure 2 Schematically illustrates the cross-sectional structure of another embodiment of the all-solid-state battery cell of the present invention. Figure 1 Similarly, in order to illustrate the positional relationship of each component, the structure of the unit is finally simplified. The conductive material 3 on the high potential side and the conductive material 4 on the low potential side are opposite to each other with the second solid electrolyte 2 as a separator sandwiched therebetween. The first solid electrolyte 1 is adjacent to the second solid electrolyte 2 and the conductive material 3 on the high potential side. Figure 2In the method, in the component constituting the conductive material 3 on the high potential side, the positive electrode active material 31 avoids direct contact with the second solid electrolyte by contacting with the first solid electrolyte 1, and the conductive material 32 other than the positive electrode active material has a portion that is in direct contact with the second solid electrolyte 2 without the aid of the first solid electrolyte 1. In addition, there is a case where the first solid electrolyte 1 completely covers the positive electrode active material 31 and is not in direct contact with the conductive material 32. When the first solid electrolyte 1 is sufficiently thin, the positive electrode active material 31 and the conductive material 32 are in electrical contact through the tunnel effect, and the positive electrode active material 31 and the conductive material 32 are at the same potential. The structure other than this is the same as the above Figure 1 The method is common.

[0154] exist Figure 2 In the embodiment, ion conduction between the second solid electrolyte 2 as a separator and the positive electrode active material 31 is performed by means of the first solid electrolyte 1. Therefore, in this embodiment, the first solid electrolyte 1 also has a function as a protective material. In addition, the positive electrode active material 31 is adjacent to the conductive material 32 other than the positive electrode active material at the surface portion not in contact with the first solid electrolyte 1, so that the conduction between the external wiring member not shown connected to the conductive material 32 other than the positive electrode active material and the positive electrode active material 31 can be ensured.

[0155] In addition, when the first solid electrolyte is as thin as tens of nanometers or less, electrons can exceed the potential barrier of the first solid electrolyte, and conduction can be ensured between the positive electrode active material 31 and the conductive material 32. Therefore, even if the positive electrode active material 31 is completely covered with the first solid electrolyte 1, there is no problem in the battery structure.

[0156] As Figure 2 A representative example of the method is the case where the positive electrode active material powder is formed by covering the surface of the particles of the positive electrode active material 31 with the first solid electrolyte 1 as a protective material. In this case, in an actual all-solid battery, the contact portion between the positive electrode active material 31 and the conductive material 32 other than the positive electrode active material corresponds to the portion where the particles of the conductive auxiliary agent (e.g., stainless steel, carbon) penetrate the covering layer as the protective material and are electrically connected to the positive electrode active material 31.

[0157] As a specific example, when the positive electrode active material powder is completely covered with the first solid electrolyte 1, and the thickness of the first solid electrolyte (layer) is as thin as less than tens of nanometers, even if a contact portion as in the previous item is not provided, the conductive aid and the positive electrode active material can ensure conductivity through the tunnel effect.

[0158] The ion-conducting material (solid electrolyte) between the particles of the buried positive electrode active material 31 conducts ions with the help of a covering layer composed of the first solid electrolyte 1 that functions as a protective material, so the second solid electrolyte 2 (sulfide, etc.) of the same type as the separator can be used as the aforementioned ion-conducting material. Figure 2 In the embodiment, the portion of the second solid electrolyte 2 in contact with the first solid electrolyte 1 is considered to be equivalent to the particles of the second solid electrolyte 2 as the positive electrode material filling the gaps between the particles of the positive electrode active material 31. The particles of the second solid electrolyte 2 are in contact with the particles of the second solid electrolyte 2 constituting the layer of the separator and bear ion conduction. That is, Figure 2 The portion denoted by reference numeral 2 corresponds to a portion in which particles of the second solid electrolyte 2 serving as a separator and particles of the second solid electrolyte 2 serving as a positive electrode material buried between particles of the positive electrode active material 31 are collectively described.

[0159] In short, it is preferred that the conductive material on the high potential side includes a positive electrode active material and other conductive members, the positive electrode active material is in contact with the first solid electrolyte, and the positive electrode active material is not in contact with the second solid electrolyte.

[0160] The decomposition voltage of the all-solid-state battery cell of this embodiment is 4.5 V or higher and the ion conductivity is 5×10 -11 S / cm or more. Preferably, the decomposition voltage is 5.0 V or more and / or the ion conductivity is 5×10 -10 S / cm or more.

[0161] [3. Lithium-ion secondary battery]

[0162] The technical concept of the present invention is also reflected in the lithium-ion secondary battery that effectively utilizes the all-solid-state battery cell of this embodiment. As a specific structure other than the all-solid-state battery cell in the lithium-ion secondary battery, a known structure can be adopted (for example Figure 3 ).

[0163] [4. Method for producing solid electrolyte powder]

[0164] 《Method for producing dry solid electrolyte powder》

[0165] Figure 4 This is a flow chart of the method for producing the solid electrolyte powder of the present invention.

[0166] The method for producing solid electrolyte powder (dry method) according to the present embodiment mainly has the following configuration.

[0167] A mixed powder obtaining step of dry-mixing the Li raw material, the Nb raw material, and the P raw material in an inert atmosphere with a dew point of -20°C or less to obtain a mixed powder; a calcining step of calcining the mixed powder at 350°C or less in an air atmosphere

[0168] As the amount of raw materials, 0.7 to 5 mass % of Li raw material, 8 to 60 mass % of Nb raw material and 1.0 to 30 mass % of P raw material are dry mixed with respect to the obtained mixed powder. Then, a solid electrolyte powder having a crystallite diameter of 100 nm or less (preferably amorphous, hereinafter referred to as "amorphous") is produced.

[0169] The contents that overlap with those described in [1. Solid electrolyte powder] are omitted below. The mass % expression structure and molar ratio expression structure described in [1. Solid electrolyte powder] can also be applied to the amount of Li raw material, Nb raw material, and P raw material input as the method for producing solid electrolyte powder. In addition, in the method for producing solid electrolyte powder, the amount of non-oxygen surplus (10% by mass or less) described in [1. Solid electrolyte powder] can also be applied.

[0170] As the Li raw material, lithium compounds such as lithium hydroxide, lithium oxide, and lithium nitrate are preferably prepared. As the Li raw material, lithium oxide is preferably used. The reason is that lithium oxide is classified as a mesh-modified oxide of a glass-forming oxide, and Nb2O5 as an intermediate oxide is easily amorphous by coexisting with lithium oxide, and a solid electrolyte powder with a crystallite diameter of less than 100 nm is easily obtained.

[0171] As the Nb raw material, it is preferred to prepare niobium oxides such as NbO, NbO2, and Nb2O5·nH2O. The solid electrolyte powder obtained by using Nb2O5·nH2O, which is an intermediate oxide of the glass-forming oxide, is easy to become amorphous and easy to obtain a solid electrolyte powder with a crystallite diameter of 100 nm or less, so it is preferred.

[0172] As the P raw material, phosphorus compounds such as phosphorus pentoxide, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate are preferably prepared. As the P raw material, phosphorus pentoxide (P2O5) is preferred. This is because phosphorus pentoxide is a mesh-forming oxide of a glass-forming oxide, and the mixed powder is easily amorphous, and a solid electrolyte powder with a crystallite diameter of less than 100 nm is easily obtained.

[0173] As a preferred example of the combination of the above-mentioned raw materials, there is mentioned a case where the above-mentioned Li raw material is lithium oxide, the above-mentioned Nb raw material is hydrated niobium oxide, and the above-mentioned P raw material is phosphorus pentoxide.

[0174] (Weighing process)

[0175] The Li raw material, the Nb raw material, and the P raw material are weighed so that the obtained solid electrolyte powder satisfies the above-mentioned composition expressed in mass % and / or composition expressed in molar ratio.

[0176] (Mixed powder obtaining process)

[0177] In the method for producing the solid electrolyte powder of the present embodiment, raw materials containing Li, Nb, and P as solid substances are mechanically mixed. The mechanical mixing can be performed by a method of pulverizing and mixing using a pulverizer such as a dry ball mill.

[0178] The time of pulverization and mixing is preferably set in the range of 1 to 50 hours so that the two substances can be fully mixed. The particle size of the mixed powder is preferably 5 to 50 μm as described above.

[0179] The atmosphere in the mixing container is preferably set to an inert gas atmosphere such as argon or nitrogen with a dew point of less than -20°C (preferably a dew point of less than -40°C). If the dew point of the atmosphere is less than -20°C, the reaction between the moisture in the atmosphere and the P raw material can be suppressed. As a result, the generation of phosphoric acid, which may become an obstacle to obtaining amorphous materials, can be suppressed, and a solid electrolyte powder with a crystallite diameter of less than 100 nm can be obtained. The dew point of the atmosphere in the mixing container can be set to, for example, more than -100°C, more than -90°C, or more than -80°C.

[0180] (Baking process)

[0181] The mixed powder obtained by the mechanical mixing is calcined to synthesize an amorphous powder containing Li, Nb, and P. The calcination atmosphere is preferably set to air. The calcination temperature is preferably set to a range of 150 to 350° C. As the lower limit of the calcination temperature, 200° C. is preferably used. The calcination time can be set within a range of, for example, 0.5 to 10 hours. The heating rate from room temperature to the calcination temperature can be set to 5 to 15° C. / minute.

[0182] (Crushing process)

[0183] The calcined powder obtained in the calcining step may be further pulverized. The particle size of the pulverized powder in this case is preferably 5 to 50 μm as described above.

[0184] 《Method for producing a covering liquid for covering a positive electrode active material with a first solid electrolyte (wet method)》

[0185] Fig. 9 This is a flow chart for coating a positive electrode active material with a first solid electrolyte using the coating solution of the present invention.

[0186] The covering liquid can be manufactured as follows. That is, in the method for manufacturing an aqueous solution (covering liquid) containing polyacid ions, lithium ions and phosphate ions of niobium of the present invention, hydrated niobium oxide is used as a starting material of niobium. After dissolving hydrated niobium oxide and LiOH in water to obtain an aqueous solution containing polyacid ions and lithium of niobium, phosphate ions are added to the aqueous solution to obtain an aqueous solution containing polyacid ions, lithium ions and phosphate ions of niobium. This process is also referred to as a covering liquid manufacturing process.

[0187] Hereinafter, the wet type is described by the element name or compound name instead of the element symbol.

[0188] In the present invention, an aqueous coating solution may be used to coat the positive electrode active material powder with the first solid electrolyte 1. As the aqueous coating solution of lithium niobate, a precursor aqueous solution of lithium niobate using polyacid ions having excellent chemical stability is used.

[0189] Furthermore, the niobium polyacid ions that are once soluble in the alkali side maintain the polyacid form even when phosphoric acid is added and the pH of the system is lowered to about 4. The aqueous solution containing niobium polyacid ions, lithium ions, and phosphate ions of the present invention contains niobium in the form of polyacid and therefore has excellent storage stability.

[0190] The reason why the increase in the specific surface area covering the positive electrode active material is suppressed when the polyacid ions of niobium and phosphate ions coexist in the lithium ion aqueous solution is not clear at present, but the present inventors speculate as follows.

[0191] That is, the presence of phosphate ions contained in the aqueous solution containing polyacid ions of niobium, lithium ions and phosphate ions improves the wettability of the aqueous solution to the surface of the positive electrode active material. The double-layer structure of the interface changes and the structure of the covering layer changes by the action of phosphate ions contained in the aqueous solution with excellent storage stability. Alternatively, by using stable polyacid ions, the generation of gas that is a cause of pores can be suppressed, and further, the trace amount of phosphate ions contained in the covering layer suppresses the generation of pores in the covering layer during drying.

[0192] Therefore, by using the coating liquid of the present invention, the coverage rate is high and uniform coating can be achieved.

[0193] [Nb source]

[0194] Since anhydrous niobium oxide (Nb2O5) is poorly soluble in water, in the manufacturing method of the present invention, amorphous and water-soluble hydrated niobium oxide is used as a Nb source. The hydrated niobium oxide is a substance represented by the general formula Nb2O5·nH2O (n is not 0, for example, 3≤n≤16).

[0195] [Polyacid ions]

[0196] Polyacids are anionic species formed by condensation of oxygen-containing acids, and polyacids of transition metal elements can be regarded as molecular ionic species of metal oxides. It should be noted that when the metal element is one, it is called isopolyacid, and when the metal element is multiple, it is called heteropolyacid.

[0197] The potential-pH diagram of niobium has not yet been established, but niobium hydroxide precipitates in the neutral region, so it is believed that solid phases such as Nb(OH)5 and HNbO3 are stable chemical species in this pH region.

[0198] If a base is added to the aqueous solution containing these solid phases to increase the pH of the system, the excess OH - ions, and niobium, for example, in the form of Nb(OH)6 - 、NbO3 - It is believed that if the pH of the system is further increased, the soluble niobium oxide will adopt various condensation states depending on the pH of the system, but in this specification, it is believed that the niobium oxide that is soluble on the alkaline side will also become polyacid ions of niobium. It should be noted that the polyacid ions of niobium that are once soluble on the alkaline side will maintain the polyacid form even if phosphoric acid is added and the pH of the system is lowered to about 4.

[0199] The aqueous solution of polyacid ions, lithium ions and phosphate ions containing niobium of the present invention contains niobium in the form of polyacid, and thus has excellent storage stability. The form of niobium can be any soluble polyacid ion, and its structure is not particularly limited.

[0200] The presence of niobium in aqueous solution in the form of polyacid ions can be confirmed by FT-IR measurement. When niobium in aqueous solution is in the form of polyacid ions, the wavelength of the niobium ions is 850 cm -1 ±20cm -1 An absorption peak due to the Nb-O bond was observed nearby.

[0201] [Lithium hydroxide]

[0202] In the production method of the present invention, lithium hydroxide (LiOH) is used as a Li source. LiOH may be anhydrous or hydrated. In the production method of the aqueous solution containing polyacid ions of niobium, lithium ions and phosphate ions of the present invention, it is characterized in that LiOH is initially added to the aqueous solution containing niobic acid to dissolve the niobic acid.

[0203] Since LiOH itself is a strong base, if LiOH is added to an aqueous solution containing niobic acid, the pH of the system rises, niobium oxide dissolves, and niobium polyacid ions are stably formed. Then, hydrogen peroxide is added to the alkaline aqueous solution containing niobium polyacid ions and lithium ions. The effect of hydrogen peroxide will be described later.

[0204] When the molar ratio of Li, Nb and P in the aqueous solution containing niobium polyacid ions, lithium ions and phosphate ions of the present invention is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65 and z is 5-65.

[0205] It is believed that the niobium in the aqueous solution containing polyacid ions, lithium ions and phosphate ions of the present invention mainly adopts the form of relatively stable polyacid. If hydrogen peroxide is added to the aqueous solution, the storage stability is further improved. The aqueous solution of the present invention does not contain organic matter, so a coating layer with low volume resistivity can be finally obtained.

[0206] [Phosphate ion]

[0207] The main technical feature of the present invention is that phosphate ions coexist in an aqueous solution containing polyacid ions of niobium and lithium ions. As a supply source of phosphate ions, water-soluble phosphoric acid (PO4 3- ) salt. Phosphoric acid is a tribasic acid and undergoes three-stage dissociation in an aqueous solution. Therefore, it can exist in various forms such as phosphate ions, monohydrogen phosphate ions, dihydrogen phosphate ions, and pyrophosphate ions in an aqueous solution. However, its existence form is not determined by the type of the drug used as a supply source of phosphate ions, but by the pH of the aqueous solution. Therefore, the above-mentioned ions containing a phosphate group are collectively referred to as phosphate ions.

[0208] As the content of phosphate ions in the aqueous solution containing polyacid ions of niobium, lithium ions and phosphate ions, according to the above molar ratio expression, z is 5 to 65 as described above, preferably 10 to 45. If z is 5 or more, the effect of adding phosphate ions is sufficient. If z is 65 or less, the effect of adding phosphate ions is not saturated.

[0209] The sum of the contents of lithium, niobium and phosphorus in the aqueous solution containing polyacid ions, lithium ions and phosphate ions of niobium is preferably 1% by mass or more and 20% by mass or less. More preferably, it is 3% by mass or more and 10% by mass or less. If the sum of the contents of lithium, niobium and phosphorus is 1% by mass or more, in order to obtain the desired film thickness of the coating layer, the amount of the aqueous solution containing polyacid ions, lithium ions and phosphate ions of niobium does not need to be increased, and the amount of water does not need to be increased, which is cost-effective. If the sum of the contents of lithium, niobium and phosphorus is 20% by mass or less, the viscosity of the aqueous solution containing polyacid ions, lithium ions and phosphate ions of niobium is appropriate, which can suppress the clogging of the thin piping of the device used for the coating treatment.

[0210] The amount of impurity elements other than lithium, niobium, phosphorus, oxygen and hydrogen in the aqueous solution containing polyacid ions of niobium, lithium ions and phosphate ions is preferably 10% by mass or less. More preferably, it is 1% by mass or less. As a specific example of an impurity element, nitrogen can be cited, and the amount of nitrogen is preferably 0.1% by mass or less, 0.01% by mass or less, 0.001% by mass or less, 0.0001% by mass or less (1ppm), and 0.1ppm or less, in that order. In addition, carbonate ions and the like are considered as unavoidable impurities. It should be noted that, here, impurities refer to impurities contained in the evaporation residue when the precursor aqueous solution is evaporated to dryness at 200°C.

[0211] [Hydrogen peroxide]

[0212] In order to improve storage stability, hydrogen peroxide may be further added to the aqueous solution of the present invention. In this case, it is preferably added in such a manner that the concentration of hydrogen peroxide in the aqueous solution becomes 0.01 mass % or more and 10 mass % or less. If the concentration of hydrogen peroxide is 0.01 mass % or more, it is possible to suppress the generated polyacid of niobium from reacting with hydroxide ions and decomposing. In addition, if it is 10 mass % or less, it is possible to suppress the generated polyacid of niobium from reacting with hydrogen peroxide and decomposing.

[0213] It should be noted that the molar ratio of hydrogen peroxide to niobium addition (POA / Nb) is preferably set in the range of 0.1 or more and 1 or less. By setting it to 0.1 or more, it is advantageous to avoid the polyacid of niobium from reacting with hydroxide ions and decomposing. On the other hand, by setting it to 1 or less, the generated polyacid of niobium reacts with hydrogen peroxide and is easily decomposed.

[0214] From the viewpoint of reactivity, the addition of hydrogen peroxide is preferably performed after the hydrated niobium oxide is dissolved together with LiOH to form stable niobium polyacid ions. It should be noted that the addition of phosphate ions and the addition of hydrogen peroxide in this item may be performed first.

[0215] Here, the added hydrogen peroxide decomposes over time, but preferably contains 0.01 mass % or more and 6.7 mass % or less in terms of hydrogen peroxide in the aqueous solution. If the hydrogen peroxide is 0.01 mass % or more, the effect of maintaining the stability of the precursor aqueous solution can be appropriately exerted. In addition, if the hydrogen peroxide is 6.7 mass % or less, the effect of adding hydrogen peroxide will not be saturated.

[0216] In addition, the ratio of the number of moles of hydrogen peroxide calculated from the concentration of hydrogen peroxide and the niobium concentration in the aqueous solution to 1 mole of niobium (POC / Nb) is preferably in the range of 0.01 to 1. If it is within the above range, not only will the effect of hydrogen peroxide addition not be saturated, but also the positive electrode active material will not be dissolved when used as a covering liquid. If hydrogen peroxide is present in an appropriate amount and not too little, it is possible to suppress the polyacid of niobium from reacting with hydroxide ions and decomposing. A further preferred range of POC / Nb is 0.05 to 0.5.

[0217] [pH]

[0218] In the manufacturing method of the present invention, the pH of the aqueous solution when forming niobium polyacid ions is approximately automatically determined by the amount of LiOH added as a strong base, the amount of phosphoric acid added, and the amount of hydrogen peroxide added, so there is no need to specifically adjust the pH, and it becomes 7.5 to 12.5 on the alkaline side. In order to stably form niobium polyacid ions, the more preferred pH is 9.0 to 12.0. When phosphoric acid is added to the solution containing niobium polyacid and lithium, the pH of the system decreases, but it is confirmed that niobium polyacid exists stably when the pH is 3 or above. The pH of the solution to which phosphoric acid is added is preferably 12.5 or less. More preferably, it is 12 or less. It should be noted that the pH value here is a value measured using a glass electrode using a pH meter equipped with a temperature compensation electrode and calibrated based on JIS Z8802 using an appropriate buffer solution corresponding to the pH range to be measured.

[0219] The method of using a covering liquid to cover a positive electrode active material with a solid electrolyte in this embodiment mainly has the following structure. The following structure is also technically significant as a method for manufacturing a covering body formed by covering a positive electrode active material with a solid electrolyte. Each example described in this specification can be applied to the content described in this paragraph.

[0220] A phosphate ion adding step of adding phosphate ions to an aqueous solution containing polyacid ions of niobium and lithium; a covering step of bringing the aqueous solution obtained by the adding step into contact with a positive electrode active material to cover the surface of the positive electrode active material with a solid electrolyte

[0221] When the molar ratio of Li, Nb and P in the aqueous solution obtained by the adding step is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65.

[0222] Through the above steps, the surface of the positive electrode active material is covered with at least one of the following solid electrolytes. As a result, a covering body is obtained.

[0223] i) A solid electrolyte containing 0.7 to 5 mass % Li, 8 to 60 mass % Nb, and 1.0 to 30 mass % P relative to a solid electrolyte, wherein the content of non-oxygen remainder other than oxygen, i.e. O, in the remainder is less than 10 mass % relative to the solid electrolyte, and the crystallite diameter is less than 100 nm.

[0224] ii) When the molar ratio of Li, Nb and P is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, z is 5 to 65, and the crystallite diameter is 100 nm or less.

[0225] The specific form of the covering step is shown in Example 10 described later. Fig. 9 The positive electrode active material mixing step in the embodiment is not limited to a specific method as long as the coating liquid and the positive electrode active material are mixed. The same is true for the drying step, and the specific method is not limited to a specific method.

[0226] In this project, the case where the positive electrode active material powder is covered with the first solid electrolyte 1 using an aqueous solution-based covering liquid is described. On the other hand, the solid electrolyte powder can also be obtained from the covering liquid. The method mainly has the following structure. Each example described in this specification can be applied to the content described in this paragraph.

[0227] A phosphate ion adding step of adding phosphate ions to an aqueous solution containing polyacid ions of niobium and lithium; and a drying step of drying the aqueous solution obtained in the adding step to obtain a solid electrolyte powder.

[0228] Furthermore, when the molar ratio of Li, Nb, and P in the aqueous solution obtained by the adding step is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65.

[0229] In addition, similarly to the solid electrolyte powder obtained by a dry process, an all-solid-state battery cell can be produced using the solid electrolyte powder.

[0230] <Modifications, etc.>

[0231] Above, one mode of the present invention has been described, but the above disclosure represents an illustrative mode of the present invention. That is, the technical scope of the present invention is not limited to the above illustrative mode, and various changes can be made within the scope of the gist thereof. In addition, for the following modified examples, the above disclosure can also be arbitrarily selected and combined.

[0232] Example

[0233] Hereinafter, the present invention will be described in detail using examples, but the present invention is not limited to the following examples.

[0234] 《Dry Example: Comparative Example 1, Examples 1 to 9》

[0235] In each example, lithium oxide (Li2O manufactured by Wako Pure Chemical Industries, Ltd.), hydrated niobium oxide (Nb2O5·nH2O manufactured by HC Starck Tungsten GmbH, Nb2O5 content 56.4%), and phosphorus pentoxide (P2O5 manufactured by Wako Pure Chemical Industries, Ltd.) were weighed as Li raw material, Nb raw material, and P raw material, respectively, in the amounts shown in Table 1 below. The weighed Li raw material, Nb raw material, and P raw material were mixed with zirconium oxide balls of Φ10 mm using a planetary ball mill (P-7 manufactured by Fritsch Co., Ltd.) at 380 rpm for 24 hours in an argon atmosphere at a dew point temperature of -60°C to obtain a mixed powder.

[0236] [Table 1]

[0237]

[0238] The mixed powder was added to a hot air drying furnace and heat treated at a calcination temperature of 200°C for 5 hours to obtain a calcined powder. The calcined powder was pulverized in the atmosphere at 380 rpm while stirring for 5 hours using a planetary ball mill (manufactured by Fritsch, P-7) together with a zirconia ball of Φ10 mm. Thus, the solid electrolyte powder of each example was obtained.

[0239] In Comparative Example 1, a solid electrolyte powder was obtained in the same manner as in each Example except that the P raw material was not used and the Li raw material and the Nb raw material were weighed in the amounts shown in Table 1.

[0240] ICP measurement was performed on the solid electrolyte powder obtained in each example to quantitatively analyze the constituent elements of the solid electrolyte powder, and the contents of niobium, lithium, and phosphorus obtained by the measurement are shown in Table 2. The ICP measurement method is as follows.

[0241] [Table 2]

[0242]

[0243] 0.1 g of the calcined powder (solid electrolyte powder) obtained after the pulverization step in each example was weighed.

[0244] 1 mL of hydrofluoric acid having a concentration of 46% by mass was added to the powder sample to decompose the sample.

[0245] The decomposition solution was fixed to volume using a 100 mL volumetric flask, diluted 100 times with 5 mass % hydrochloric acid, and then the concentration of the constituent elements of the solid electrolyte powder containing niobium, lithium and phosphorus in the diluted solution was measured using an inductively coupled plasma emission spectrometer (ICP-AES, CP-720 manufactured by Agilent Technologies, Inc.).

[0246] The nitrogen content in the solid electrolyte powder obtained in each example was analyzed using a nitrogen analyzer (EMGA-920 manufactured by Horiba, Ltd.). In addition, the carbon content in the solid electrolyte powder obtained in each example was analyzed using a trace carbon sulfur analyzer (ETMA-U510 manufactured by Horiba, Ltd.). The content of the balance other than lithium, niobium, and phosphorus (i.e., non-oxygen balance) obtained from the above-mentioned ICP measurement, nitrogen content, and carbon content measurement results was 1% by mass or less in all examples.

[0247] Figure 5 This is a graph showing the composition ratios of Li, Nb, and P in the solid electrolyte powder obtained in each example expressed in terms of molar ratio.

[0248] The volume-based cumulative 50% particle size (D50) of the solid electrolyte powder obtained in each example was measured, and the measurement results are shown in Table 2.

[0249] In addition, the method of measuring the volume-based cumulative 50% particle size (D50) in this specification is as follows.

[0250] The particle size distribution of the obtained solid electrolyte powder was measured using a laser diffraction particle size distribution measuring device (HELOS H3758 & RODOS manufactured by Japan Laser Corp.) The dispersion method was air flow dispersion (nitrogen), the dispersion pressure was 5 bar, and the focal length was 200 mm.

[0251] Here, according to the evaluation method disclosed in Patent Document 2, a fully solid electrochemical cell having a structure in which a solid electrolyte (first solid electrolyte) of a test material and a sulfide-based solid electrolyte (second solid electrolyte) are adjacent to each other is prepared, and the decomposition voltage caused by the oxidation reaction of the test material is obtained. Specifically, the experiment is conducted as follows.

[0252] <1. Preparation of composite material mixture>

[0253] The solid electrolyte powders of Comparative Example and Example and stainless steel (SUS316) powder were weighed at a volume ratio of 50:50.

[0254] Then, the mixture was mixed in a mortar to prepare a composite material mixture.

[0255] <2. Fabrication of Electrochemical Cells>

[0256] 57 mg of argyrodite-type sulfide solid electrolyte (Li6PS5Cl) was added into the insulating outer cylinder.

[0257] This was press-formed at a pressure of 80 MPa, thereby obtaining a second solid electrolyte.

[0258] Next, 20 mg of the solid electrolyte of the example or the comparative example was placed on the second solid electrolyte, and pressure molding was performed at a pressure of 80 MPa to form a first solid electrolyte.

[0259] Next, 20 mg of the composite material mixture of the example and the comparative example was placed on the first solid electrolyte and press-molded at a pressure of 360 MPa to form a composite material.

[0260] Next, metal In (thickness 200 μm), metal Li (thickness 300 μm) and metal In (thickness 200 μm) were stacked in order under the second solid electrolyte (on the side opposite to the first solid electrolyte). The metal In was press-formed at a pressure of 80 MPa to form a counter electrode member consisting of a three-layer structure of In / Li / In.

[0261] Next, current collectors made of stainless steel plates were placed on the upper and lower sides of the stacked body, and current collecting leads were provided.

[0262] Through the above operations, an electrochemical battery cell is manufactured.

[0263] Figure 6 This is a graph showing the composition ratio of Li, Nb, and P in the solid electrolyte powder obtained in each example expressed by the molar ratio and the decomposition voltage as numerical values.

[0264] The electrochemical evaluation method is as follows.

[0265] The electrochemical cell was placed in a constant temperature bath at 25°C.

[0266] The voltage stability was evaluated by using a potentiostat / galvanostat (VersaSTAT4 manufactured by Prinston) as an electrochemical measuring apparatus and sweeping the voltage from the open circuit voltage of the electrochemical cell to 6.0 V (vs In-Li) (synonymous with 6.6 V (vs Li)) and measuring the reaction current.

[0267] When the voltage on the working electrode side of the electrochemical cell is swept toward the oxidation side, a current derived from a non-Faraday reaction not accompanied by electron transfer and a minute current derived from a side reaction of adsorbed water and impurities flows.

[0268] Since the current up to 4.0 V (vs Li) was relatively small at 10 μA or less and the increase amount was 10 μA / V or less, it was determined that the current was derived from the side reaction.

[0269] When a voltage exceeding 4.0 V is applied, a point at which the current value increases appears, and therefore this reaction is a current accompanying a decomposition reaction.

[0270] In this test, as a reference of the decomposition voltage, the voltage at which a current of 15 μA flows is defined as the decomposition voltage.

[0271] Figure 7 In the electrochemical evaluation of each example, the potential (unit is V (vs Li / Li + )) is the horizontal axis and the current value (unit is μA) is the vertical axis.

[0272] The method for measuring the ionic conductivity is as follows.

[0273] 0.2 g of the powder sample of each example was placed in a cylindrical container having a diameter of 10 mm, and the container was pressed at 180 MPa using a press to obtain a powder compact.

[0274] The obtained powder compact was pressed again at 300 MPa using a CIP molding machine (CPP-PS200A, CPP28-300B manufactured by NPa SYSTEM CO., LTD.), and a silver paste was applied on both surfaces to prepare a sample for ion conductivity measurement.

[0275] The ion conductivity of the obtained sample was measured by an AC impedance method in a nitrogen atmosphere at 30° C. in a range of 0.1 Hz to 4 MHz and an amplitude voltage of 500 mV using an impedance analyzer (ZENNIUM manufactured by ZAHNER).

[0276] Then, the resistance value of the sample of the embodiment was obtained from the Cole-Cole plot (complex impedance plane plot) of the measured value, and the ion conductivity was calculated from the obtained resistance value. The calculated ion conductivity value is recorded in the above Table 2. The ion conductivity is 5.0×10 -10 (S / cm) and above were recorded as very good, and ion conductivity less than 5.0×10 -10 (S / cm) and 5.0×10 -11 The case with a value of (S / cm) or above was recorded as good.

[0277] The solid electrolyte powder of each example was subjected to XRD measurement under the following measurement conditions.

[0278] Figure 8It is a graph with 2θ (unit: °) as the horizontal axis and intensity (cps) as the vertical axis in the evaluation of crystallinity in each example.

[0279] <XRD measurement conditions>

[0280] Measuring device: XRD-6100 (manufactured by Shimadzu Corporation)

[0281] Tube target: Cu (measured at the wavelength of Kα1)

[0282] Tube voltage: 40 kv

[0283] Tube current: 30 mA

[0284] Divergence slit: 1.0°

[0285] Scattering slit: 1.0°

[0286] Receiving slit: 0.3 mm

[0287] Step size: 0.02° / step

[0288] Measurement time: 0.60 sec

[0289] According to Figure 8 , a halo with a full width at half maximum of 2θ: 2° or more was observed in the XRD spectra of the solid electrolyte powders of each example in the region of 2θ: 15° to 40°. Thus, it was confirmed that the solid electrolyte powders of each example were amorphous.

[0290] As shown in Table 2, in each example, the decomposition voltage was higher than that of Comparative Example 1. As a result, in each example, it was possible to provide an all-solid battery cell and a lithium-ion secondary battery that兼顾 high lithium-ion conductivity and high decomposition voltage. That is, it was found that when using the solid electrolyte powders and their manufacturing methods of each example, it was possible to兼顾 high lithium-ion conductivity and high decomposition voltage.

[0291] 《Wet examples: Comparative Example 2, Example 10》

[0292] In order to cover the positive electrode active material with the first solid electrolyte, the following production of the first solid electrolyte covering liquid and the covering of the positive electrode active material were carried out.

[0293] As described below, the covering liquids of the first solid electrolyte of Comparative Example 2 and Example 10 were produced.

[0294] 41 g of lithium hydroxide (LiOH, manufactured by Wako Pure Chemical Industries, Ltd.) and 125 g of hydrated niobium oxide (Nb2O5·nH2O, manufactured by HC Starck Tungsten GmbH, Nb2O5 content 56.4%) were mixed with 734 g of water and stirred at a stirring speed of 200 rpm. Then, the temperature was raised to 70°C at a heating rate of 0.75°C / min and maintained at 70°C for 7 hours. After maintaining, 29 g of hydrogen peroxide was added and filtered to obtain a lithium niobate solution of Comparative Example 2. 49 g of water was added to 35 g of the obtained lithium niobate solution to obtain the covering liquid of Comparative Example 2. In addition, 48 g of water and 1.1 g of phosphoric acid (manufactured by Wako Pure Chemical Industries, phosphoric acid concentration 85% solution) were added to 35 g of the lithium niobate solution to obtain the covering liquid of Example 10.

[0295] The pH and ICP of the coating liquid obtained in each example were measured. The values ​​obtained by the measurements are shown in Table 3.

[0296] The analysis of the components of the covering liquid was performed using an inductively coupled plasma emission spectrometer (ICP-AES, Agilent Technology 700 Series). 0.1 g of the sample was taken from the precursor solution and weighed, 15 mL of pure water and 5 mL of hydrochloric acid were added thereto, and the mixture was heated and then naturally cooled. After further adding 2 mL of hydrogen peroxide solution and naturally cooling, the liquid volume was constant to 100 mL and analyzed by ICP-AES. The molar number of the present invention was calculated from the contents of niobium, lithium, and phosphorus obtained in the quantitative analysis using ICP.

[0297] In addition, in order to confirm whether the niobium in the aqueous solution of Comparative Example 2 and Example 10 is a polyacid ion, Fourier transform infrared spectroscopy (FT-IR) was performed using NICOLET7600 manufactured by ThermoFisher Scientific Inc. In order to remove the peak on the low wave number side of water as a solvent, water was used in the background measurement, and the measurement was performed by the total reflection measurement (ATR) method. A germanium prism was used in the measurement, and the incident angle was 45°. The aqueous solutions of Comparative Example 2 and Example 10 were subjected to FT-IR measurement, and the results showed that at a wave number of 850 cm -1 ±20cm -1 An absorption peak due to the Nb-O bond was observed near 1.5 Å, and it is believed that the soluble hydrated niobium oxide exists in the form of niobium polyacid ions. The FT-IR spectra of the aqueous solutions obtained in Comparative Example 2 and Example 10 are shown in FIG. Fig.10 .

[0298] [Table 3]

[0299]

[0300] The coating liquid of Comparative Example 2 and Example 10 was air-dried at 200°C to obtain a solid electrolyte powder. The powders (solid electrolyte powders) of Comparative Example 2 and Example 10 obtained after air drying were subjected to quantitative analysis of the constituent elements of the solid electrolyte powder, nitrogen content, and volume-based cumulative 50% particle size (D50) of the solid electrolyte powder in the same manner as in Example 1, and the results are recorded in Table 3. Decomposition voltage and ion conductivity were measured. The values ​​obtained by the measurements are recorded in Table 4.

[0301] [Table 4]

[0302]

[0303] The powders of Comparative Example 2 and Example 10 obtained after air drying were subjected to XRD measurement in the same manner as in Example 1. As a result, a halo with a half-peak width of 2θ: 2° or more was observed in the XRD spectrum of the solid electrolyte powder of each example in the region of 2θ: 15° to 40°. Thus, it was confirmed that the solid electrolyte powder of each example was amorphous.

[0304] Next, LiNi was prepared as a positive electrode active material powder. 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (manufactured by MTI). In addition, 4-sodium (SORB) US manufactured by Yuasa Ionics Co., Ltd. was used as the positive electrode active material powder, and the BET specific surface area obtained by the BET one-point method was 0.538 m 2 / g.

[0305] The first solid electrolyte was coated on the positive electrode active material powder using the coating liquids of Comparative Example 2 and Example 10. The coating method was as follows.

[0306] 40 g of the positive electrode active material powder was mixed with 20 g of the solution of Comparative Example 2 and Example 10 obtained above, and coated using a coating device (JD-1 manufactured by KAWATA CO., LTD.) (positive electrode active material mixing step, drying step). The coating conditions were as follows.

[0307] Slurry supply speed: 3mL / min

[0308] Dispersion air pressure: 500kPa

[0309] Dispersion air temperature: 200℃

[0310] Dry air temperature: 135℃

[0311] Drying blower air volume: 900L / min

[0312] Classification blower air volume: 890L / min

[0313] The coverage ratio when the first solid electrolyte covers the positive electrode active material powder was calculated based on the element amount measured using XPS (JPS-9200 manufactured by JEOL Ltd.). The calculation formula is shown in the following formula 1. The calculated coverage ratio is shown in Table 5.

[0314] Coverage (%) = (Nb + P) / (Ni + Co + Mn + Nb + P) × 100 (Formula 1)

[0315] [Table 5]

[0316] Covering layer thickness (nm) Coverage (%) Comparative Example 2 10 94 Example 10 10 94

[0317] In the positive electrode active material powder covered with the first solid electrolyte of this embodiment, it can be assumed that Nb and P not contained in the positive electrode active material powder exist only in the covering layer. In addition, it is considered that for the thickness of the covering layer of the positive electrode active material covered with the first solid electrolyte, Nb and P in the covering liquid are changed to Nb2O5 and P2O5, respectively, which are expressed by the following formula 2 (the same in the following examples).

[0318] When the Nb content in the covered positive electrode active material powder is set to a (mass %) and the P content is set to b (mass %), the mass ratio c (mass %) of Nb and P in the covering layer is calculated by the atomic weight of Nb and P and the molecular weight of Nb2O5 and P2O5 by the following formula. It should be noted that the Nb content and the P content are measured by the following method.

[0319] c = a × molecular weight of Nb2O5 / (atomic weight of Nb × 2) + b × molecular weight of P2O5 / (atomic weight of P × 2)

[0320] (Formula 2)

[0321] Furthermore, if the specific surface area S (m 2 / g) and the density of the first solid electrolyte (g / cm 3 ), the average film thickness t (nm) of the covering layer is expressed by the following formula. It should be noted that 10 on the right side of the following formula 3 is a conversion factor.

[0322] t(nm)=10×C / (d×S) (Formula 3)

[0323] It should be noted that the density of the first solid electrolyte is 4.13 g / cm 3 (The calculation was performed using a pycnometer MICRO-ULTRAPYC1200e manufactured by Anton Paar GmbH, which was used to measure the first solid electrolyte powder in Example 10).

[0324] In addition, the contents (mass %) of Nb and P in the positive electrode active material powder covered with the first solid electrolyte were measured as follows.

[0325] Weigh 0.1 g of the positive electrode active material powder covered with the first solid electrolyte. Add 1 mL of hydrofluoric acid with a concentration of 46% by mass to the powder sample to decompose the sample. Use a 100 mL volumetric flask to make the decomposition solution constant volume, dilute it to 100 times with 5% by mass hydrochloric acid, and use an inductively coupled plasma emission spectrometer (ICP-AES, Agilent Technologies, Inc. CP-720) to determine the concentration of the constituent elements of the positive electrode active material powder containing niobium and phosphorus in the dilution.

[0326] Fig.11 It is a schematic diagram of the cross-sectional structure of the electrochemical cell configured to investigate the discharge DCR increase rate in Comparative Example 2 and Example 10.

[0327] The following electrochemical cells were prepared using the positive electrode active material powder obtained by covering the first solid electrolyte with the covering liquid of Comparative Example 2 and Example 10. The DC internal resistance (DCR) of the electrochemical cell was measured when the prepared electrochemical cell was subjected to floating charge at a constant voltage, and the discharge DCR increase rate for evaluating the deterioration of the electrochemical cell was obtained. Specifically, the experiment was conducted as follows.

[0328] 70 mg of the positive electrode active material covered with the first solid electrolyte, 30 mg of argyrodite-type sulfide solid electrolyte (Li6PS5Cl) as the second solid electrolyte, and 3.1 mg of carbon as the conductive material were mixed in a mortar to prepare a composite material mixture.

[0329] 100 mg of argyrodite-type sulfide solid electrolyte (Li6PS5Cl) was added to the insulating outer cylinder.

[0330] This was press-formed at a pressure of 185 MPa to obtain a second solid electrolyte.

[0331] Next, 10 mg of the composite material mixture of the example and the comparative example was placed on the second solid electrolyte and press-molded at a pressure of 370 MPa to form a composite material.

[0332] Next, metal In (thickness 200 μm), metal Li (thickness 300 μm) and metal In (thickness 200 μm) were stacked in order under the second solid electrolyte (on the side opposite to the first solid electrolyte). The metal In was press-formed at a pressure of 185 MPa to form a counter electrode member consisting of a three-layer structure of In / Li / In.

[0333] Next, current collectors made of stainless steel plates were placed on the upper and lower sides of the stacked body, and current collecting leads were provided.

[0334] Through the above operations, an electrochemical battery cell is manufactured.

[0335] The battery evaluation method is as follows.

[0336] The electrochemical cell was placed in a constant temperature bath at 55°C.

[0337] Using a charge and discharge measuring device (HJ1001SD8 manufactured by Hokuto Denko), the voltage was swept from the open circuit voltage of the electrochemical cell to 3.83 V (vs In-Li) (synonymous with 4.45 V (vs Li)) and float charging was performed for 30 days.

[0338] The DCR increase rate was calculated by the following method.

[0339] After the voltage of the electrochemical cell that had been float charged for 30 days was adjusted to 3.9V (vs Li), it was discharged at 1C (C: the current value that can charge and discharge the battery cell capacity in 1 hour) for 10 seconds. The value obtained by subtracting the voltage at the beginning of the test (0th second) from the voltage at the end of the test (10th second) was divided by the current value to calculate the discharge DCR increase rate. The calculated discharge DCR increase rate is recorded in Table 6.

[0340] [Table 6]

[0341]

[0342] ※(DCR after 30 days - initial DCR) / initial DCR×100

[0343] Description of Reference Numerals

[0344] 1 The first solid electrolyte

[0345] 2. Second solid electrolyte

[0346] 3 Conductive material on the high potential side

[0347] 4 Conductive material on the low potential side

[0348] 31. Positive electrode active material

[0349] 32 Conductive materials other than positive electrode active materials

[0350] 41 Negative electrode active material

[0351] 42 Conductive materials other than negative electrode active materials

Claims

1. An all-solid-state battery cell comprising: Conductive material on the high potential side, a first solid electrolyte in contact with the conductive material on the high potential side, a second solid electrolyte in contact with the first solid electrolyte, and a conductive material on the low potential side in contact with the second solid electrolyte, The first solid electrolyte contains at least one of the following solid electrolytes (1) and (2) as a main component, The second solid electrolyte contains sulfide as a main component, (1) A solid electrolyte containing 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P relative to the solid electrolyte, wherein the content of the remainder other than oxygen, i.e., O, is 10 mass % or less relative to the solid electrolyte, and the crystallite diameter is 100 nm or less, (2) When the molar ratio of Li, Nb and P contained in the solid electrolyte is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, z is 5 to 65, and the crystallite diameter is less than 100 nm.

2. The all-solid-state battery cell according to claim 1, wherein: The first solid electrolyte is the following (3) and (4), (3) containing 0.7 to 2.6 mass % of Li, 8 to 60 mass % of Nb, and 2.0 to 30 mass % of P relative to the solid electrolyte, and When the molar ratio of Li, Nb and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less, the content of the non-oxygen remainder other than oxygen, i.e., O, in the remainder is 10% by mass or less relative to the solid electrolyte, and the crystallite diameter is 100 nm or less. (4) When the molar ratio of Li, Nb and P contained in the solid electrolyte is set to Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 30, y is 5 to 65, z is 5 to 65, and the crystallite diameter is less than 100 nm.

3. The all-solid-state battery cell according to claim 1, wherein: The conductive material on the high potential side includes a positive electrode active material and other conductive members. The positive electrode active material is in contact with the first solid electrolyte, and the positive electrode active material is not in contact with the second solid electrolyte.

4. The all-solid-state battery cell according to claim 1, wherein: The conductive material on the high potential side includes a positive electrode active material and other conductive members. The surfaces of the particles of the positive electrode active material are covered with the first solid electrolyte.

5. A solid electrolyte powder, wherein: The solid electrolyte powder contains 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P. The content of the non-oxygen balance other than oxygen, that is, O, in the balance is 10% by mass or less relative to the solid electrolyte powder. The crystallite diameter of the solid electrolyte powder is 100 nm or less.

6. The solid electrolyte powder according to claim 5, wherein The solid electrolyte powder contains 0.7 to 2.6 mass % of Li, 8 to 60 mass % of Nb, and 2.0 to 30 mass % of P, and When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 30 or less.

7. The solid electrolyte powder according to claim 5, wherein The content of the transition metal element in the non-oxygen remainder is 3% by mass or less relative to the solid electrolyte powder.

8. A solid electrolyte powder, wherein: When the molar ratio of Li, Nb, and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65. The crystallite diameter of the solid electrolyte powder is 100 nm or less. 9 . The solid electrolyte powder according to claim 8 , wherein the content of non-oxygen surplus other than oxygen (O) in the surplus is 10% by mass or less relative to the solid electrolyte powder.

10. The solid electrolyte powder according to claim 8, wherein x is 15-30, y is 5-65, and z is 5-65. 11 . The solid electrolyte powder according to claim 5 , wherein the total mass % of Li, Nb, and P in the solid electrolyte powder is in the range of 25 to 65 mass %.

12. The solid electrolyte powder according to any one of claims 5 to 10, wherein The particle size of the solid electrolyte powder is 5 to 50 μm, which is a volume-based cumulative 50% particle size (D50) obtained using a laser diffraction scattering particle size distribution measuring device. 13 . The solid electrolyte powder according to claim 5 , which is used for an all-solid-state battery cell.

14. An all-solid-state battery cell comprising: Conductive material on the high potential side, a first solid electrolyte in contact with the conductive material on the high potential side, a second solid electrolyte in contact with the first solid electrolyte, and a conductive material on the low potential side in contact with the second solid electrolyte, The first solid electrolyte contains the solid electrolyte powder according to any one of claims 5 to 10 as a main component, The second solid electrolyte contains sulfide as a main component.

15. A method for producing a solid electrolyte powder, which is the method for producing a solid electrolyte powder according to claim 5 or 8, comprising: A step of dry-mixing a Li raw material, a Nb raw material, and a P raw material in an inert atmosphere with a dew point of -20°C or less to obtain a mixed powder; and The mixed powder is calcined at 350° C. or lower in an air atmosphere.

16. The method for producing a solid electrolyte powder according to claim 15, wherein: The Li raw material is lithium oxide, the Nb raw material is hydrated niobium oxide, and the P raw material is phosphorus pentoxide.

17. A method for producing a solid electrolyte powder, which is the method for producing a solid electrolyte powder according to claim 5 or 8, comprising: a phosphate ion adding step of adding phosphate ions to an aqueous solution containing polyacid ions of niobium and lithium; and a drying step of drying the aqueous solution obtained in the adding step to obtain a solid electrolyte powder, When the molar ratio of Li, Nb and P in the aqueous solution obtained by the above-mentioned adding step is Li:Nb:P=x:y:z (x+y+z=100), x is 15-50, y is 5-65, and z is 5-65.

18. A method for manufacturing a covering, comprising: A step of adding phosphate ions to an aqueous solution containing polyacid ions of niobium and lithium to obtain an aqueous solution in which x is 15 to 50, y is 5 to 65, and z is 5 to 65 when the molar ratio of Li, Nb, and P in the aqueous solution is Li:Nb:P=x:y:z (x+y+z=100); and a covering step of bringing the aqueous solution obtained in the above step into contact with a positive electrode active material to cover the surface of the positive electrode active material with a solid electrolyte, The solid electrolyte satisfies at least one of the following conditions: i) containing 0.7 to 5 mass % of Li, 8 to 60 mass % of Nb, and 1.0 to 30 mass % of P relative to the solid electrolyte, The content of the non-oxygen balance other than oxygen, that is, O, in the balance is 10% by mass or less relative to the solid electrolyte, and Solid electrolytes with crystallite diameters below 100 nm, ii) when the molar ratio of Li, Nb and P is Li:Nb:P=x:y:z (x+y+z=100), x is 15 to 50, y is 5 to 65, and z is 5 to 65, and Solid electrolyte with a crystallite diameter of less than 100nm.

Citation Information

Patent Citations

  • All-solid lithium battery

    WO2007004590A1

  • Positive electrode material, and battery

    WO2020174868A1